Study of Investors Decisions for Investment Avenues based on Their Risk and Return Profile: A Select Study Conducted at Uttar Pradesh - Shivam Bhardwaj, Dr. Ankit Saxena (International Journal of Advanced Science and Technology, 2020)
With the change in time, investment norms, guidelines, policies, and facilities- financial markets nowadays are offering better opportunities to invest. In India large numbers of small investors are there who have the potential to invest in the stock market, gold or silver, real estate, fixed deposits, post office deposits, insurance, etc. Many researches have been conducted during the past years to understand the investor’s perception of various investment options available. However there is a gap or vacuum in terms of micro studies focusing on specific cities or states in India. The objectives of the study are to study the impact of the demographic profile of the investors in Agra on their risk perception towards various alternative opportunities and to know about investors preferences toward investment. Convenient snowball sampling was conducted for research, and the responses were received using a structured questionnaire. An appropriate statistical analysis was performed over the data collected using SPSS. Results revealed the point that the most prominent reasons for investment are principal stability and growth of income.